Integrated Marketing Communications (IMC) strategies analysis at PT. Eshan Mega Propertindo - Karina Imelia Irfani; Arianis Chan; Pratami Wulan Tresna (Eduvest - Journal of Universal Studies, 2024)
Integrated Marketing Communication (IMC) is the process of developing and implementing various forms of persuasive communication programs to customers and potential customers on an ongoing basis. Therefore, the aim of this research is to analyze the strategy for implementing Integrated Marketing Communication at PT. Eshan Mega Propertindo. This research method is descriptive qualitative. This research uses key informants to obtain the required information. The data used is primary data and secondary data. Primary data was obtained from interviews with the director of PT. Eshan Mega Propertindo regarding company profile and secondary data obtained from IMC implementation data in the company. At the data analysis stage, researchers used SWOT analysis. The result of this research is an analysis of integrated marketing communication strategies in advertising, sales promotion, public relations, sponsorship and direct marketing activities. Based on the results of research and analysis carried out by the author, it can be concluded that the data obtained from interviews were processed using IFE and EFE mat rix analysis and the results obtained were that the company had a strength of 1,72, weekness of 1,38, opportunities of 2,00 and threats of 1,60. It can be concluded that the company is in quadrant I of the SWOT analysis.